The Effect of Boron Concentration on the Properties and Paraselectivity of Zeolite HZSM-5 in the Methylation Reaction of Ethylbenzene - Gahramanov, Taleh Ordukhan; Mammadova, Ayten Zakir; Akhmedova, Nargiz Firudin; Mamedov, Sabit Eyyub; Kerimli, Fuad Shamsaddin; Ahmadov, Eldar Isa (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
In order to increase the selectivity for p-ethyltoluene, catalytic systems based on HZSM-5 zeolite modified with orthoboric acid were obtained, which were used in the alkylation of ethylbenzene with methanol. The reaction was carried out in a continuous flow reactor with a fixed catalyst bed in the temperature range of 300-400 °C at atmospheric pressure to study the effect of boron concentration in the composition of HZSM-5 on the selectivity of the formation of ethyltoluenes and p-ethyltoluene. Physicochemical and textural characteristics of the catalysts were characterized by X-ray Diffraction (XRD), Infra Red (IR) spectroscopy, NH3-Temperature Program Desorption (TPD) and low-temperature Nitrogen Adsorption (NA). It was found that the decrease in the density of strong acid sites, reduction in the volume of micropores and increase in the mesoporosity of zeolite as a result of modification are the main reasons for the enhancement of the catalyst selectivity to p-ethyltoluene. Catalyst 5 %B-HZSM-5 in the temperature range of 300 - 350 °C with conversion of ethylbenzene equal to 14.7-18.4 % shows a sufficiently high selectivity for p-ethyltoluene (60.5-70.2 %). Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).